PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Derliana Siregar; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine and analyze the effect of capital structure and profitability of the company's value in the food and beverage sector listed in Indonesia Stock Exchange. Where the independent variable X1 is an indicator of capital structure with a debt to asset ratio (DAR) and debt equity ratio (DER), then to the independent variable X2 is profitabilitas with indicator of the return on investment (ROI) and return on equity (ROE). The dependent variable is the value of a company in the indicator Price to Book Value (PBV) in the food and beverage sector listed in Indonesia Stock Exchange. The data used in this research is secondary data derived from financial statements food and beverage sectors listed in Indonesia Stock Exchange. Sampling was done by purposive sampling and samples that meet the selection criteria. The samples used were as many as seven companies. Analysis of data using multiple linear regression analysis to test the statistical hypothesis testing and statistical tests f t-aided software SPSS 21. The results of this study indicate that capital structure partially (t test) did not significantly affect the value of companies in the food and beverage sector Indonesian securities listed on the exchange. The results of the study simultaneously (f test) showed a significant effect of the variable capital structure and profitability of the company's value in the food and beverage sector listed in Indonesia Stock Exchange. Keywords. Capital Structure (DAR and DER), Profitability (ROI and ROE), Company Value (PBV)